2019
DOI: 10.1111/cei.13382
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal anti-dsDNA antibody 2C10 escorts DNA to intracellular DNA sensors in normal mononuclear cells and stimulates secretion of multiple cytokines implicated in lupus pathogenesis

Abstract: There have been many studies on the mechanisms of internalization of DNA-anti-DNA immune complexes by cells, including the one used for rheumatoid factor-expressing mouse B cells. In parallel, studies on the role of intracellular DNA sensors in the pathogenesis of systemic lupus erythematosus (SLE) have been conducted, including the one using a mouse model lacking one of the sensors. These and other data have established a framework for understanding the pathogenic role of anti-DNA antibodies, but studies on n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…59,60 There is ample evidence that IgG immune complexes are transported through Fc receptors into lysosomes. [61][62][63] Therefore, it can be assumed that catalytic antibodies that hydrolyze RNA and miRNAs, along with RNase T2 and RNase 2, are involved in the activation of TLR7 and TLR8. Moreover, it is known that some antibodies can enter the cell through interaction with receptors or antigens.…”
Section: Discussionmentioning
confidence: 99%
“…59,60 There is ample evidence that IgG immune complexes are transported through Fc receptors into lysosomes. [61][62][63] Therefore, it can be assumed that catalytic antibodies that hydrolyze RNA and miRNAs, along with RNase T2 and RNase 2, are involved in the activation of TLR7 and TLR8. Moreover, it is known that some antibodies can enter the cell through interaction with receptors or antigens.…”
Section: Discussionmentioning
confidence: 99%
“…Why WB-6 induces TF but 2C10 or H241 do not is a puzzle. Recently we reported that 2C10-DNA complex is incorporated by monocytes through macropinocytosis, and that the DNA stimulates the TLR9 and AIM-2 pathways resulting in expression of several inflammatory cytokines relevant to SLE pathogenesis [30]. We usually observe that 2C10 enters live cells more readily than WB-6 even at low concentrations as shown in Figure 2.…”
Section: Discussionmentioning
confidence: 91%
“…Similarly, the highly expressed mammalian target of rapamycin (mTOR) in lupus mice has also been shown to induce lupus nephritis (LN) through activation of mTOR/mitochondrial ROS/NLRP3 signaling ( 108 ). Another function of anti-dsDNA Abs is to help DNA in the plasma or on the cell surface enter normal monocytes through endocytosis to activate the AIM2 inflammasome, forming a vicious cycle of SLE pathogenesis ( 109 ). Naik et al.…”
Section: Role Of Pyroptosis In Autoimmune Diseasesmentioning
confidence: 99%